IRON REGULATORY PROTEINS MEDIATE HOST RESISTANCE TO SALMONELLA INFECTION - Nairz, Manfred (Cell Host Microbe, 2015)
Macrophages are essential for systemic iron recycling, and also control iron availability to pathogens. Iron metabolism in mammalian cells is orchestrated post-transcriptionally by iron-regulatory proteins (IRP)-1 and -2. Here, we generated mice with selective and combined ablation of both IRPs in macrophages to investigate the role of IRPs in controlling iron availability. These animals are hyperferritinemic but otherwise display normal clinical iron parameters. However, mutant mice rapidly succumb to systemic infections with Salmonella Typhimurium, a pathogenic bacterium that multiplies within macrophages, with increased bacterial burdens in liver and spleen. Ex vivo infection experiments indicate that IRP function restricts bacterial access to iron via the EntC and Feo bacterial iron-acquisition systems. Further, IRPs contain Salmonella by promoting the induction of lipocalin 2, a host antimicrobial factor that inhibits bacterial uptake of iron-laden siderophores, and by suppressing the ferritin iron pool. This work reveals the importance of the IRPs in innate immunity.